THE PROBLEM OF ECOLOGICAL CONSCIOUSNESS AS A SUBJECT OF PSYCHOLOGICAL RESEARCH (American Journal of Research in Humanities and Social Sciences, 2024)
This article discusses research questions devoted to the study of increasing the effectiveness of methods of forming environmental representations in students and improving their methodological aspects.